Geniposide Alleviates Amyloid-Induced Synaptic Injury by Protecting Axonal Mitochondrial Trafficking - Zhang, Haijing; Zhao, Chunhui; Lv, Cui; Liu, Xiaoli; Du, Shijing; Li, Zhi; Wang, Yongyan; Zhang, Wensheng (Frontiers in Cellular Neuroscience, 2017)
Synaptic and mitochondrial pathologies are early events in the progression of Alzheimer's disease (AD). Normal axonal mitochondrial function and transport play crucial roles in maintaining synaptic function by producing high levels of adenosine triphosphate and buffering calcium. However, there can be abnormal axonal mitochondrial trafficking, distribution, and fragmentation, which are strongly correlated with amyloid-β (Aβ)-induced synaptic loss and dysfunction. The present study examined the neuroprotective effect of geniposide, a compound extracted from gardenia fruit in Aβ-treated neurons and an AD mouse model. Geniposide alleviated Aβ-induced axonal mitochondrial abnormalities by increasing axonal mitochondrial density and length and improving mitochondrial motility and trafficking in cultured hippocampal neurons, consequently ameliorating synaptic damage by reversing synaptic loss, addressing spine density and morphology abnormalities, and ameliorating the decreases in synapse-related proteins in neurons and APPswe/PS1dE9 mice. These findings provide new insights into the effects of geniposide administration on neuronal and synaptic functions under conditions of Aβ enrichment.